Nitrous oxide labor analgesia and pain relief memory in breastfeeding women. (17th December 2018) - Zanardo, Vincenzo; Volpe, Francesca; Parotto, Matteo; Giiberti, Lara; Selmin, Alessia; Straface, Gianluca
Abstract: Objective: The use of labor pain relief medications is a controversial issue that has engendered heated discussions among health care professionals about safety, interference with birthing, and breastfeeding. Methods: This is a case–control study with 62 puerperae treated with nitrous oxide and 124 control women (ratio 1:2), matched for age, gestational age, parity, delivery route, labor augmentation, and spinal regional analgesia. We tested anhedonia, anxiety, and depression symptoms at hospital discharge by The Edinburgh Postnatal Depression Scale (EPDS), and the intensity of nitrous oxide labor pain relief and satisfaction memory by a retrospective Visual Analog Scale (VAS, 0–10 Numeric Rating Scale) at a set cut off time of 3 months of a child's age. Results: Nitrous oxide use did not influence EPDS subscales upon discharge. Its use was instead associated with a lasting positive labor pain relief experience (VAS, 7.3 ± 2.2) in 83.5% of women, and labor satisfaction memory (VAS, 8.9 ± 1.8) in 90% of women, respectively, and with a significantly higher breastfeeding rates from the seventh day after discharge ( p  < .031), to the 1st ( p  < .043), and the third month of life ( p  < .016). Conclusions: Nitrous oxide labor analgesia is associated with favorable effects on both women's psychoemotional experience of labor and breastfeeding success.